BY MEANS OF APPLYING BASIC GOOGLE SERVICES - Оliinyk Л.М. (Journal of Information Technologies in Education (ITE), 2015)
This publication presents industry experience of Google services in the Regional Institute of Postgraduate Education. As well training courses are offered for the organization of blended learning and to improve ICT competence of teachers. Postgraduate Education aids as the improvement of education and specialized training of teachers by strengthening, expanding and updating their professional knowledge and skills. Improving ICT competence of educators is employed as an urgent task for the state teachers who work in the system of Postgraduate Education. Google provided opportunities to study the organization of working in blended forms and improve educators in ICT competence. Improving ICT competence of teachers employed allows them to keep up with modern and future technologies and to keep up with their students as well they will be able to guide them along. As a result of applying basic Google services there was an increase of the level of ICT competence, increased motivation to use all of their professional skills, and also acquired information and communication technologies were increasing distribution of those skills by teachers in communities Google+. Despite the fact that connecting their professional interests,teachers acquired knowledge and skills to work on educational blogs and websites Google. Information and communication technologies are developing extremely fast. With basic services, Google’s applications in postgraduate education teachers are able to improve their personal skills replacing the board and chalk, notebook and pen as well as being able to work together with other teachers and colleagues in Google-forms, Google-tables, and Google-presentations. Instead of searching for information in any old-fashioned library now we have an opportunity to research and find information by means of using electronic resources in more comfortable and self-regulating way.